Evaluation and Validation of a Model for Predicting Pavement Structural Number with Rolling Wheel Deflectometer Data. Issue 1 (January 2015) - Elseifi, Mostafa A.; Gaspard, Kevin; Wilke, Paul W.; Zhang, Zhongjie; Hegab, Ahmed
Because of costs and the slow test process, the use of structural capacity in pavement management activities at the network level has been limited. The rolling wheel deflectometer (RWD) was introduced to support existing nondestructive testing techniques by providing a screening tool for structurally deficient pavements at the network level. A model was developed to estimate structural number (SN) from RWD data obtained in a Louisiana study. The objective for this study was to evaluate the use of the Louisiana model to predict structural capacity in Pennsylvania and to compare the results with those of existing methods. RWD testing was conducted on 288 mi of the road network in Pennsylvania, and falling weight deflectometer (FWD) testing and coring were conducted on selected sites. The prediction from a model used to estimate SN from RWD deflection data was compared statistically with the prediction obtained from FWD testing and from roadway management system records used by the Pennsylvania Department of Transportation to calculate SN. The results of this analysis validated the use of the model to estimate the pavement SN according to RWD deflection data. In general, the predicted SN was in agreement with the SN calculated from the FWD. The original model with the fitted coefficients developed for Louisiana showed an average prediction error of 27%. However, after the model was refitted to the data set from Pennsylvania, the average error dropped to 19%. Results indicated that the model developed for SN prediction from the RWD provided an adequate prediction of SN for conditions different from those for which it was developed in Louisiana.